Digital marketing for dummies - Deiss, Ryan; Henneberry, Russ (John Wiley & Sons, 2017)
Written with the marketer's best interests in mind, this friendly, down-to-earth guide shows you how to use proven digital marketing strategies and tactics to expand the reach of your brand, increase audience engagement, and acquire and monetize customers. --
Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed February 10, 2017)
Keywords: Internet marketing; Internet advertising; Web site development; Marketing sur Internet; Publicité sur Internet; Sites Web; Développement